APPLICATION OF THUMB MANAGEMENT IN IMPROVING THE MARKETING PERFORMANCE OF DROPSHIPPERS - Sakdiyah , Halimatus; Uyun, Jamilatul (Prosiding Seminar Nasional dan Call Paper STIE Widya Wiwaha, 2023)
The objective of this research is to investigate the implementation of dropshipper's thumb management in enhancing marketing performance. The research employed a qualitative methodology, focusing on dropshippers in Pamekasan Regency as the research subjects. The research findings on the implementation of online business management by dropshippers indicate that there is still room for improvement. The dropshippers have not fully concentrated on their online business endeavors, resulting in suboptimal outcomes in planning, organizing, directing, and controlling. However, they have managed to enhance their marketing performance by adopting an online business orientation, which involves innovation, risk-taking, and proactive actions. As a result, the sales volume of their products has been steadily increasing year after year. Moreover, they have successfully achieved customer growth in line with their objectives, leading to an increase in the profits generated from product sales.